The opioid crisis in North America: facts and future lessons for Europe - Kennedy Ayoo; John Mikhaeil; Alexander Huang; Marcin Wąsowicz (Anaesthesiology Intensive Therapy, 2020)
Over the past two decades, opioid-related hospitalizations and deaths in North America have reached the level of a public health emergency. Initially, the epidemic of opioid misuse was largely driven by pharmaceutical companies and initiated by their spread of misinformation, which led physicians to engage in overzealous prescribing behaviour. This was followed by significant harms as deaths related to overdoses on prescription and illicit opioids rose steadily throughout the 1990s and early 2000s. This review examines the historical context of the opioid crisis in the United States and Canada, the role of physicians, the contributions of the pharmaceutical industry and the evolution of the epidemic in response to the introduction of highly potent synthetic opioids now recognized as the main culprits in opioid overdose and death. This article further explores the evidence surrounding the effectiveness of various treatment strategies and harm-reduction interventions designed to curtail the morbidity and mortality associated with opioid use. Finally, the magnitude of the opioid epidemic in North America is compared to that in European countries. This paper describes the differences in North American and European experiences with opioid overdose and the evidence-based approaches that can be implemented to reduce the mortality and morbidity linked to opioids while simultaneously ensuring adequate pain control for patients.